Compensation for Damages Resulting from Remote Healthcare Services - Alkutubi, Moza; Bin Sagheer, Murad (Journal of Legal Sciences, 2026)
The harms of remote health care services constitute another aspect and a new chapter of medical liability in its successive developments. These damages often result from smart or automated remote health services. This study comes to shed light on the mechanism for compensating damages from remote health care services and the necessity of covering them. By highlighting the concept of telehealth services, its controls, and explaining the most prominent applications of these damages, as well as addressing the idea of compensating for them. This is done by clarifying the basis of compensation and the criteria for its assessment, in addition to its scope and forms, to ensure comprehensive and fair reparation for the damage. The study concluded several results, the most prominent of which are: the specificity of the damages caused by telehealth services, their difference from traditional medical damages, as well as the inadequacy of traditional compensation rules to cover new medical damages. In addition to the urgent need to review the current compensation systems and adapt them in a way that allows for coverage and compensation of emerging damages for telehealth services. This is what prompted us to include some recommendations, the most important of which are: the necessity of reviewing and qualifying the legal texts regulating the provisions of compensation and civil liability in general, in addition to filling the legislative shortcomings of the Medical Liability Law of 2016, in a way that allows the damages of telehealth services to be absorbed and covered.